Removal Of Colour, Cod And Nh3-N From Semi-Aerobic Sanitary Landfill Leachate Using Sulfonic Acid And Quaternary Amine Functional Group Resins - Bashir, Mohammed J. K. (2011)

(untitled)
The application of ion exchange process in landfill leachate treatment was not well established in literature. Optimized operational conditions and the interaction among process variables for this treatment process were unidentified, leaving a substantial gap in landfill leachate treatment knowledge. In the present study, the treatment of stabilized landfill leachate using resin- cationic, anionic, cationic followed by anionic (cationic-anionic), and anionic followed by cationic (anionic-cationic) were established and documented for the first time.